Maqasid Al-Syariah as the Foundation for the Development of Contemporary Islamic Law - Zihan Fauziah; Anita Dewi; Olivia Tiara Dewi (Anthroposia: Journal of Social and Human Development, 2026)
This study examines Maqasid Al Shariah as a foundational framework for the development of contemporary Islamic law in response to changing social, economic, institutional, and regulatory realities. Employing a non empirical library research design with a normative conceptual approach, the study analyzes classical and contemporary scholarly works to explore the theoretical foundations, operational functions, and future relevance of maqasid based legal reasoning. The findings indicate that Maqasid Al Shariah has evolved from a doctrinal theory of legal objectives into a comprehensive framework that guides contemporary ijtihad, legal interpretation, and institutional governance. The study demonstrates that maqasid facilitates the adaptation of Islamic law to contemporary issues in family law, Islamic finance, banking governance, economic fatwas, social development, and environmental sustainability while preserving the normative integrity of Shariah principles. The analysis also reveals significant challenges arising from interpretative diversity, legal pluralism, globalization, digital transformation, and regulatory complexity. Despite these challenges, the maqasid approach provides a coherent mechanism for balancing textual authority with contextual realities. The study concludes that Maqasid Al Shariah remains a dynamic and transformative foundation for sustainable Islamic legal reform and contemporary legal development.